A dispersão entre metrópoles : atuação do segmento habitacional do setor imobiliário no aglomerado urbano de Jundiaí - Baldusco, Lacir Ferreira (2015)
Our goal is to discuss the Sparse City through the actions of the Real Estate Segment with no pretension to exhaust this complex topic. From the premise that the city should be seen as a market’s byproduct to understand the valuation of urban land and its occupation. Our focus is the Urban Cluster of Jundiaí. For its economic dynamism and urban sprawl this area is part of the state planning virtual territory of the São Paulo Macrometropolitan Area. The data presented here outlines the urban landscape during the verticalization process of core municipalities, more specifically in the consolidated urban areas. These core municipalities are spreading the borders through the horizontal real estate, IE, through the deployment of subdivisions and housing developments on its fringes. This process produces and disseminates the ideas which aim to hide the real production processes of uneven urban spaces, sells the image of the new, the novelty in the style of life and how to live, when in fact express the old forms of ownership of the urban landscape. This work seeks to discuss the criteria and consequences of using old instruments of division of land, based on a speculative culture generated by both public investment and the real estate capital. These two old forces are responsible for the cities we live in today and that reproduce continually a model that does not help the quality of life of its inhabitants. Finally, using the information obtained from the GRAPROHAB (the state agency that oversees the licensing of all housing) public and private enterprises, it is possible to show the trend in vertical integration in the most dynamic and prosperous cities as a decisive factor for the spatial segregation of urban land.